2011
DOI: 10.1177/1533317511421921
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-e4, Processing Speed, and White Matter Volume in a Genetically Enriched Sample of Midlife Adults

Abstract: Healthy midlife children of a parent with Alzheimer's disease ([AD] N = 23; 9 male) participated in neuropsychological testing, and magnetic resonance imaging (MRI) of brain volumetrics were obtained. In all, 35% of the sample were apolipoprotein E (ApoE)-e4 positive (n = 8; 5 male). The ApoE-e4 group exhibited significantly slower performances on an executive function and processing speed measure and had less white matter volume than the non-ApoE-e4 group. Lesser white matter volume was significantly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Age is the most important risk factor for AD, but surprisingly, apoE4 genotype impacts cognition even in healthy, non-demented, and young individuals (9,10). Also, whereas longitudinal cognitive decline is steeper in apoE4 carriers (11,12,68), numerous reports have shown that the effect of apoE4 on cognition is actually greater in younger than in older subjects (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Age is the most important risk factor for AD, but surprisingly, apoE4 genotype impacts cognition even in healthy, non-demented, and young individuals (9,10). Also, whereas longitudinal cognitive decline is steeper in apoE4 carriers (11,12,68), numerous reports have shown that the effect of apoE4 on cognition is actually greater in younger than in older subjects (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…This greater neural recruitment by the MS group relative to healthy controls was interpreted to be consistent with the neural efficiency hypothesis, further supporting the belief that more connections must be recruited to maintain performance in the presence of brain pathology. Similarly, Ready and colleagues (2011) noted decreased white matter volume to be significantly correlated with slower processing speed in a sample of healthy midlife children of a parent with Alzheimer's disease. The authors concluded PS and changes in white matter volume to be potential indicators of preclinical decline in Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 88%
“…Healthy individuals with ApoE4 are characterised by less white matter volume (Ready et al, 2011) (age = 53) and a higher rate of myelin breakdown in an older sample (Bartzokis et al, 2006) (age = 66). Furthermore, ApoE4 carriers have also showed decreased FA in widespread white matter tracts associated with temporal lobe structures, including the cingulum (Smith et al, 2010) (age = 58), corpus callosum, and longitudinal fasciculus (Heise et al, 2011;Lyall et al, 2014).…”
Section: Apolipoprotein E4 and Family Historymentioning
confidence: 99%